Produção de forragem e desempenho animal em pastagem de estrela africana sobressemeada com gramíneas hibernais - Auache Filho, Alexandre Augusto (2020)
The present work aimed to evaluate the effects of the use of irrigation and intercropping with legumes on forage production and animal performance in pastures of African star (Cynodon nlemfuensis) overspread with winter grasses (Black oats, Avena strigosa Schreb and Azevém, Lolium multiflorum ) and / or legumes (cornichão, Lotus corniculatus). The experimental design used was completely randomized, with four treatments composed of G = Gramínea (African Star, Black Oats and Azevém); GL = Grasses (African star, black oats and ryegrass) + Legumes (Cornichão); GI = Grasses (African star, black oats and ryegrass) + Irrigation; GLI = Grasses (African Star, Black Oats and Ryegrass) + Legumes (Cornichão) + Irrigation, containing three replicates for each treatment. The experiment was carried out between August 2018 and March 2019, at the Research and Teaching Center in Ruminants (NEPRu) of the Experimental Unit for Beef Cattle of the Federal Technological University of Paraná, Campus of Dois Vizinhos. The treatments were distributed in an area of 3.5 ha with an area of 0.29 ha for each repetition, which were subdivided into 4 paddocks of the same size, with grazing in a rotational stocking method. The animals used were Angus-Nelore blood, with 24 tester animals being used, all castrated and with an average weight of 203 kg. For pasture, total forage production, daily accumulation rate, botanical and structural composition and nutritional value were evaluated. Animal performance was determined through the average daily gain (GMD), live weight gain per hectare and animal load. No significant differences were observed for forage production and daily accumulation rate between treatments, however the mass of oat stalks was higher for the GLI treatment, during the winter period, being 52,15% higher than the GI treatment. For the variables PB, NDF and DIVMS there was no difference between treatments in any of the seasons, with a difference only for the levels of FDA during winter and summer, where the GLI treatment during winter was less than the other treatments. During the summer the GL treatment showed lower levels of FDA compared to the other treatments. GMD during the summer period was superior for GLI treatment. The gain per hectare and animal load were similar between the treatments evaluated.